The challenges bisexual husbands face in trying to keep their marriage together: a case study in Malaysia - Mohd Rafizey Dalin; Nur Hafizah Yusoff; Azlina Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Bisexual men who are married to heterosexual women and at the same time have alternative relationships with same-sex partners are an invisible community in society, especially in Malaysia. A marriage involving one of these non-heterosexual partner such bisexual men will only be known when a divorce or marriage annulment case is settled in court. In Malaysia, although there are statistics that showcase divorce or annulment of marriages, the reality is that there are still “mixed-orientation couples” who manage to maintain their marriages to this day. To maintain a marriage, of course, there are challenges faced by them, which are the focus of this study. A total of 15 informants who claimed to have a bisexual orientation and were legally married to a heterosexual woman were interviewed in depth. The results of the study are divided into two main themes, namely, internal challenges and external challenges. Internal challenges include unsatisfying sex life, controlling men-sex-men addiction, financial matters, and negative’s attitudes from wives, while external challenges only family in-laws involvement. Overall, the findings of this study are expected to be used by government agencies responsible for empowering families, such as the Department of Religion and the Ministry of Women, Family, and Community Development, will design and help married bisexual men navigate their distinct challenges, encouraging more fulfilling marital relationships. They can enhance their relationship, promote understanding, and assure the duration and happiness of their marriage by doing so.